Prevention of canine ocular thelaziosis (Thelazia callipaeda) with a combination of milbemycin oxime and afoxolaner (Nexgard Spectra®) in endemic areas in France and Spain - Lebon Wilfried; Guillot Jacques; Álvarez Maria-Jesús; Antonio Bazaga José; Cortes-Dubly Marie-Laure; Dumont Pascal; Eberhardt Marianne; Gómez Héctor; Pennant Olivier; Siméon Noémie; Beugnet Frederic; Halos Lénaïg (Parasite, 2019)
In the past decade, canine thelaziosis due to Thelazia callipaeda has been diagnosed in an increasing number of European countries, with endemic areas being identified. A multi-center field trial was conducted in endemic areas in France and Spain to evaluate the efficacy of monthly administrations of the oral milbemycin oxime/afoxolaner combination (NexGard Spectra®) for the prevention of T. callipaeda infection in at-risk dogs. A total of 79 dogs negative for T. callipaeda and with a clinical history of eyeworm infection in the past two years completed the study. Dogs were randomly allocated either to a negative control group (42 dogs) or to the NexGard Spectra® treated group (37 dogs). All dogs were followed up for a 6-month period and assessed monthly for the presence of nematodes on the eyes and for the signs of ocular thelaziosis (e.g., conjunctivitis, keratitis, and ocular discharge). When the presence of nematodes was confirmed, the conjunctival fornix was flushed with a saline solution for parasite recovery and counting, and the dogs were treated appropriately. Recovered parasites were stored in 70% alcohol for subsequent morphological identification. During the course of the study, 57.1% (24/42) of the control dogs were diagnosed positive for Thelazia infection, which illustrates a high incidence rate of parasite infection. Conversely, no eyeworm was recovered from any of the 37 dogs that received NexGard Spectra®. All parasites sampled were confirmed to be T. callipaeda. This clinical field study demonstrated that monthly administrations of NexGard Spectra® provided 100% preventive efficacy against canine thelaziosis.